Morphology and SSU rDNA sequences of four cyrtophorian ciliates from China, with description of a new species (Protista, Ciliophora, Phyllopharyngea) - Wang, Congcong; Qu, Zhishuai; Hu, Xiaozhong (Zootaxa, 2019)
Four cyrtophorian ciliates, Chlamydodon pararoseus sp. n., Chlamydodon bourlandi Qu et al., 2018, Dysteria crassipes Claparède & Lachmann, 1859, and Dysteria monostyla (Ehrenberg, 1838) Kahl, 1931, isolated from coastal waters off China, were investigated using morphological and SSU rDNA sequencing techniques. C. pararoseus sp. n. can be recognized by having a kidney-shaped body, a complete cross-striated band, 44–51 somatic kineties, and 11–14 nematodesmal rods. The other three species were re-described based on new populations. Additionally, the SSU rRNA genes of C. pararoseus sp. n. and D. monostyla were sequenced for the first time. Phylogenetic analyses inferred from SSU rRNA gene sequences reveal that C. pararoseus sp. n. has a close relationship with C. bourlandi and C. mnemosyne Gong et al., 2005 within the genus Chlamydodon; and D. monostyla and D. crassipes cluster with its congeners, which confirms their generic assignments.